Negative impact of face masks in patients with interstitial lung disease: A prospective study - Mohr, Arno; Zahn, Stefanie; Geismann, Florian; Blaas, Stefan; Pfeifer, Michael; Malfertheiner, Maximilian; Salzberger, Bernd; Hanses, Frank; Bauernfeind, Stilla; Koch, Myriam; Hitzenbichler, Florian (Pneumologie, 2024)
Face masks increase airway resistance, data on the actual extent of this effect are scarce. The aim of this study was to assess the effect of different mask types on clinical parameters during moderate exercise in healthy non-smokers, active smokers and patients with interstitial lung disease (ILD) without the need of oxygen therapy.In a prospective observational pilot study participants performed a six-minute walk test without mask, with a surgical mask, a well-fitted FFP2 mask and with a valved FFP3 mask. Respiratory rate, blood pressure, heart rate, blood gas analysis parameters, dyspnoea and six-minute walk distance were measured. Data were analysed in an ANOVA model.21 healthy participants, 17 active smokers without known pulmonary disease and 15 patients with interstitial lung disease were included. Participants with ILD had a significant lower walking distance, a higher respiratory rate and a lower pO2 when using FFP2 masks, but not with valved FFP3 masks or surgical masks compared to not wearing a mask.For patients with ILD without the need of oxygen therapy wearing an FFP2 mask had a negative impact on pO2, respiratory rate and walking distance in the six-minute walk test. This effect was not seen with valved FFP3 masks or surgical masks.
Keywords: N95; respirator; surgical mask; interstitial lung disease; mask